Wykorzystanie symulacji w ocenie efektywności projektu inwestycyjnego - Kopiński, Adam (Usage of simulation in investment appraisal, 2006)
The investment appraisal tends to be more and more complex and it is necessary to take into account the ex-ante size of parameters (of both economic and financial aspects) as a starting point of the assessment process. Accepting these presumptions, as well as uncertainty and risk which are often caused by a long-term investment horizon, results in altered values of parameters in the decision- -making and unquestionably in the mid-term phase of the project realization. Therefore, it is indispensable to utilize simulation tools that work out a range of possible variants of the investment project realization in order to choose the most probable scenario.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 189-195